The natural products magnetic resonance database (NP-MRD): comprehensive resource for natural products NMR data enabling discovery and understanding - John R. Cort; Jessica L. Bade; Roger G. Linington; Matthew Pin; Ella F. Poynton; Lloyd W. Sumner; James T. Koller; Zachary M. Tretter; Bharat Goel; David S. Wishart; Vasuk Gautam; Scott McKay; et al. (Phytochemistry Letters, 2025)

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Bee-Ing positive about wasp-negative media reporting: the opinions of scientists and their influence on the media - C. A. Oi; R. L. Brown; S. Sumner (Insectes Sociaux, 2024)
Insects are the most diverse group on earth, providing a vast array of essential functions for people and nature. Yet, our appreciation of their contributions is biased towards a few economically important taxa, especially pollinating insects like honeybees. Other taxa are less well appreciated despite the important roles they play, and these taxa are rarely (if ever) the focus of conservation initiatives. Here, we explore the role that scientists play through their interactions with the media in shaping our attitudes towards one of the least appreciated insects—the aculeate (stinging) wasps. Vespine wasps are an excellent taxonomic group for such a study as they are important predators in native ecosystems (e.g., the Northern Hemisphere—in Europe and North America) but ecologically devastating as invasive species in many regions of the Southern Hemisphere (e.g., New Zealand, Australia, South America). Despite this, global media coverage of wasps invariably focuses on and emotively exaggerates the negative defensive stinging behaviour of wasps, and almost entirely overlooks their beneficial positive roles (as pest controllers and pollinators). Wasp and bee scientists from around the world were surveyed about their interactions with the media and how they considered these interactions to influence public perceptions and insect conservation. Our surveys capture the negative-wasp and positive-bee biases experienced by scientists through their interactions with the media. We consider the implications of such biases on wasp populations, their conservation and management, and make recommendations for a more balanced portrayal of this important and diverse group of insects.

The impact of auditory distraction on learning and task performance in working dogs - Elizabeth L. Sheldon; Carla J. Hart; Daniel S. Mills; Carl D. Soulsbury; Rebecca Sumner; Anna Wilkinson (Applied Animal Behaviour Science, 2023)

Do common dispersal influences inform a large lizard’s landscape-scale gene flow? - Tim S. Jessop; Peter Smissen; Jennifer R. Anson; Craig Sherman; Joanna M. Sumner (Evolutionary Ecology, 2022)

Responses of Southern Ocean Seafloor Habitats and Communities to Global and Local Drivers of Change - Madeleine J. Brasier; David Barnes; Narissa Bax; Angelika Brandt; Anne B. Christianson; Andrew J. Constable; Rachel Downey; Blanca Figuerola; Huw Griffiths; Julian Gutt; Susanne Lockhart; Simon A. Morley; et al. (Frontiers in Marine Science, 2021)
Knowledge of life on the Southern Ocean seafloor has substantially grown since the beginning of this century with increasing ship-based surveys and regular monitoring sites, new technologies and greatly enhanced data sharing. However, seafloor habitats and their communities exhibit high spatial variability and heterogeneity that challenges the way in which we assess the state of the Southern Ocean benthos on larger scales. The Antarctic shelf is rich in diversity compared with deeper water areas, important for storing carbon (“blue carbon”) and provides habitat for commercial fish species. In this paper, we focus on the seafloor habitats of the Antarctic shelf, which are vulnerable to drivers of change including increasing ocean temperatures, iceberg scour, sea ice melt, ocean acidification, fishing pressures, pollution and non-indigenous species. Some of the most vulnerable areas include the West Antarctic Peninsula, which is experiencing rapid regional warming and increased iceberg-scouring, subantarctic islands and tourist destinations where human activities and environmental conditions increase the potential for the establishment of non-indigenous species and active fishing areas around South Georgia, Heard and MacDonald Islands. Vulnerable species include those in areas of regional warming with low thermal tolerance, calcifying species susceptible to increasing ocean acidity as well as slow-growing habitat-forming species that can be damaged by fishing gears e.g., sponges, bryozoan, and coral species. Management regimes can protect seafloor habitats and key species from fishing activities; some areas will need more protection than others, accounting for specific traits that make species vulnerable, slow growing and long-lived species, restricted locations with optimum physiological conditions and available food, and restricted distributions of rare species. Ecosystem-based management practices and long-term, highly protected areas may be the most effective tools in the preservation of vulnerable seafloor habitats. Here, we focus on outlining seafloor responses to drivers of change observed to date and projections for the future. We discuss the need for action to preserve seafloor habitats under climate change, fishing pressures and other anthropogenic impacts.

High reproductive skew in the Neotropical paper wasp Polistes lanio - R. J. Southon; A. N. Radford; S. Sumner (Insectes Sociaux, 2020)

Morphological and molecular evidence of population divergence in a widespread shorebird across its southern mainland Australian distribution - Michael A. Weston; Kylea Clarke; Grainne S. Maguire; Joanna Sumner (Conservation Genetics, 2020)

Behavioural and neurogenomic responses of host workers to social parasite invasion in a social insect - A. Cini; R. Branconi; S. Patalano; R. Cervo; S. Sumner (Insectes Sociaux, 2020)
The strong coevolutionary arms race between social parasites and their hosts has dramatically shaped the life-history traits of both parties. One of the main strategies exhibited by hosts in response to parasitism is reproduction by host workers. We lack a mechanistic understanding of how these defence strategies unfold and, specifically, whether hosts exhibit more subtle strategies to reduce the costs of parasitism from the outset. Here we test the hypothesis that there are both behavioural and neurogenomic signatures of worker responses to parasitism, prior to overt expression in the form of egg-laying; we test this using the social parasite—social host system of the paper wasps Polistes sulcifer-Polistes dominula. We characterized individual workers’ position within the social interaction network of queenright and host colonies immediately after parasite usurpation, weeks before the workers’ reproductive rebellion is evident. Parasitism influenced network centrality measures, with workers in parasitized colonies showing increased connectedness and centrality compared to those in unparasitized ones. Next, we quantified brain gene expression levels for five genes related to physiological and behavioural phenotypes in Polistes wasps. The gene Imaginal disc growth factor ( Idgf4 ), thought to be responsive to changes in the social environment, was significantly down-regulated in workers from parasitized colonies; this may be an indication that parasitized workers are anticipating a shift toward a less worker-like phenotype in preparation for their reproductive rebellion. Our results provide the first evidence of early behavioural and neurogenomic responses of host workers toward the presence of an inquiline social parasite in a social insect.

Role of Selenoproteins in Bacterial Pathogenesis - Sarah E. Sumner; Rachel L. Markley; Girish S. Kirimanjeswara (Biological Trace Element Research, 2019)

Medicago truncatula Oleanolic-Derived Saponins Are Correlated with Caterpillar Deterrence - Fanping Cai; Bonnie S. Watson; David Meek; David V. Huhman; Daniel J. Wherritt; Cecile Ben; Laurent Gentzbittel; Brian T. Driscoll; Lloyd W. Sumner; Jacqueline C. Bede (Journal of Chemical Ecology, 2017)

Validation of a Metallomics Analysis of Placenta Tissue by Inductively-Coupled Plasma Mass Spectrometry - James M. Harrington; Daniel J. Young; Rebecca C. Fry; Frank X. Weber; Susan S. Sumner; Keith E. Levine (Biological Trace Element Research, 2016)

Development of an Analytical Method for Assessment of Silver Nanoparticle Content in Biological Matrices by Inductively Coupled Plasma Mass Spectrometry - Eric P. Poitras; Michael A. Levine; James M. Harrington; Amal S. Essader; Timothy R. Fennell; Rodney W. Snyder; Sherry L. Black; Susan S. Sumner; Keith E. Levine (Biological Trace Element Research, 2015)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Analysis of Human Serum and Whole Blood for Mineral Content by ICP-MS and ICP-OES: Development of a Mineralomics Method - James M. Harrington; Daniel J. Young; Amal S. Essader; Susan J. Sumner; Keith E. Levine (Biological Trace Element Research, 2014)

Fine‐scale spatial genetic structure of common and declining bumble bees across an agricultural landscape - Stephanie Dreier; John W. Redhead; Ian A. Warren; Andrew F. G. Bourke; Matthew S. Heard; William C. Jordan; Seirian Sumner; Jinliang Wang; Claire Carvell (Molecular Ecology, 2014)
Land‐use changes have threatened populations of many insect pollinators, including bumble bees. Patterns of dispersal and gene flow are key determinants of species' ability to respond to land‐use change, but have been little investigated at a fine scale ( Bombus species ( B. terrestris , B. lapidarius , B. pascuorum and B. hortorum ) and one declining species ( B. ruderatus ) in an agricultural landscape in Southern England, UK . The study landscape contained sown flower patches representing agri‐environment options for pollinators. We found that, as expected, the B. ruderatus population was characterized by relatively low heterozygosity, number of alleles and colony density. Across all species, inbreeding was absent or present but weak ( F IS = 0.01–0.02). Using queen genotypes reconstructed from worker sibships and colony locations estimated from the positions of workers within these sibships, we found that significant isolation by distance was absent in B. lapidarius , B. hortorum and B. ruderatus . In B. terrestris and B. pascuorum , it was present but weak; for example, in these two species, expected relatedness of queens founding colonies 1 m apart was 0.02. These results show that bumble bee populations exhibit low levels of spatial genetic structure at fine spatial scales, most likely because of ongoing gene flow via widespread queen dispersal. In addition, the results demonstrate the potential for agri‐environment scheme conservation measures to facilitate fine‐scale gene flow by creating a more even distribution of suitable habitats across landscapes.

Mountain barriers and river conduits: phylogeographical structure in a large, mobile lizard (Varanidae: Varanus varius ) from eastern Australia - Peter J. Smissen; Jane Melville; Joanna Sumner; Tim S. Jessop (Journal of Biogeography, 2013)
Aim Across eastern Australia, mountain ranges (the Great Dividing Range) and river catchments (the Murray–Darling Basin) are likely to have shaped the phylogeographical structure of many species. We address how such processes have influenced the phylogeography of the lace monitor, Varanus varius , a large mobile lizard. Location Eastern and south‐eastern Australia. Methods Phylogeographical hypotheses were tested using up to 90 museum and field‐collected samples from across the entire species' range; a 671‐bp region of the mtDNA gene ND4 was sequenced and all individuals were genotyped (eight microsatellite loci). Results Maximum‐likelihood analysis of sequence data revealed three geographically separate clades, with divergences estimated to have occurred during the Pleistocene. The south‐eastern clade showed an expansion pattern from northern refugia and dispersal appears to have occurred along the Murray–Darling river system. Microsatellite analyses support mtDNA clades but indicate secondary contact in the Hunter Valley, New South Wales. Main conclusions Our results indicate that phylogeographical structure and contemporary gene flow in Varanus varius is shaped by dispersal capacity, geographical barriers and the presence of ancient river corridors. Indeed, only the most significant geological (McPherson Range) and habitat barriers (Burdekin Gap) appear to limit gene flow in this species. The expansion of the clade on the western side of the Great Dividing Range suggests that ancient riparian corridors have facilitated extensive gene flow. Our study highlights the importance of understanding a species' ecological dynamics when examining broad‐scale evolutionary patterns.

Case study on potential agricultural responses to climate change in a California landscape - L. E. Jackson; S. M. Wheeler; A. D. Hollander; A. T. O’Geen; B. S. Orlove; J. Six; D. A. Sumner; F. Santos-Martin; J. B. Kramer; W. R. Horwath; R. E. Howitt; T. P. Tomich (Climatic Change, 2011)

Variability of Albedo and Utility of the MODIS Albedo Product in Forested Wetlands - David M. Sumner; Qinglong Wu; Chandra S. Pathak (Wetlands, 2011)

Erratum to: Overlapping functional anatomy for working memory and visual search - Elaine J. Anderson; S. K. Mannan; G. Rees; P. Sumner; C. Kennard (Experimental Brain Research, 2011)

Overlapping functional anatomy for working memory and visual search - Elaine J. Anderson; S. K. Mannan; G. Rees; P. Sumner; C. Kennard (Experimental Brain Research, 2010)

Involvement of prefrontal cortex in visual search - E. J. Anderson; S. K. Mannan; M. Husain; G. Rees; P. Sumner; D. J. Mort; D. McRobbie; C. Kennard (Experimental Brain Research, 2007)

Methyl jasmonate and yeast elicitor induce differential transcriptional and metabolic re-programming in cell suspension cultures of the model legume Medicago truncatula - Hideyuki Suzuki; M. S. Srinivasa Reddy; Marina Naoumkina; Naveed Aziz; Gregory D. May; David V. Huhman; Lloyd W. Sumner; Jack W. Blount; Pedro Mendes; Richard A. Dixon (Planta, 2005)

The evolution of social parasitism in Acromyrmex leaf-cutting ants: a test of Emery?s rule - S. Sumner; D. K. Aanen; J. Delabie; J. J. Boomsma (Insectes Sociaux, 2004)

Effects of contralateral sound stimulation on unit activity of ventral cochlear nucleus neurons - S. E. Shore; C. J. Sumner; S. C. Bledsoe; J. Lu (Experimental Brain Research, 2003)

An estimate of the effects of climate change on the rainfall of Mediterranean Spain by the late twenty first century - G. N. Sumner; R. Romero; V. Homar; C. Ramis; S. Alonso; E. Zorita (Climate Dynamics, 2003)